2021
DOI: 10.1097/cmr.0000000000000748
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein as a biomarker for immune-related adverse events in melanoma patients treated with immune checkpoint inhibitors in the adjuvant setting

Abstract: The objective of this study was to evaluate the utility of serum C-reactive protein (CRP) as biomarker for the early diagnosis of immune-related adverse events (irAEs) in melanoma patients treated with immune checkpoint inhibitors (ICIs) in the adjuvant setting, and its potential correlation with relapse-free survival (RFS). Prospectively collected data from 72 melanoma patients treated with adjuvant ICIs were pooled. CRP values at diagnosis of 10 irAEs were descriptively analysed. Correlations between RFS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
3
15
1
Order By: Relevance
“…CRP and IL-6 levels are also associated with the occurrence of irAEs. Patients with melanoma displayed elevated CRP levels when irAEs occurred, and with a CRP level more than twice the ULN were more likely to have irAEs than those with a CRP level less than the ULN (35,36). In a case report, the baseline CRP level increased from 14.2 to 138.9 mg/L when pneumonitis occurred (37).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…CRP and IL-6 levels are also associated with the occurrence of irAEs. Patients with melanoma displayed elevated CRP levels when irAEs occurred, and with a CRP level more than twice the ULN were more likely to have irAEs than those with a CRP level less than the ULN (35,36). In a case report, the baseline CRP level increased from 14.2 to 138.9 mg/L when pneumonitis occurred (37).…”
Section: Discussionmentioning
confidence: 95%
“…In fact, many of these cytokines have been implicated in the inflammation underlying autoimmune diseases (21,(31)(32)(33)(34). C-reactive protein (CRP) and IL-6, which are commonly used clinical indicators of inflammation and autoimmune diseases, have been proven to be associated with the occurrence of irAEs in melanoma and non-small cell lung cancer patients; however, the changes in the levels of these factors in liver cancer patients who experienced irAEs are unclear (35)(36)(37)(38)(39). Furthermore, whether an adverse event is an irAE must be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Several serum markers like CRP, LDH, and fecal calcitonin and their association with CIC prognosis have been investigated. Justine et al revealed that patients with elevated CRP level had a higher risk of irAE recurrence (223). LDH ≥618 IU/L was related to a poor prognosis in CIC patients (60).…”
Section: Prognosismentioning
confidence: 99%
“…As thyroid irAEs are more common and generally occur earlier than renal irAEs, this phenomenon should be considered and prompt the concurrent evaluation of thyroid status when AKI occurs during ICI therapy. CRP has shown promise as a non-invasive biomarker for the early detection of selected irAEs [ 5 , 6 ] and to discriminate between ICI related AKI from other causes [ 7 ]. Interestingly, the median CRP level was not elevated in ICI-thyroiditis in one series [ 5 ].…”
mentioning
confidence: 99%
“…CRP has shown promise as a non-invasive biomarker for the early detection of selected irAEs [ 5 , 6 ] and to discriminate between ICI related AKI from other causes [ 7 ]. Interestingly, the median CRP level was not elevated in ICI-thyroiditis in one series [ 5 ]. While elevated CRP by itself is not diagnostic of irAE due to its poor specificity, we propose that a non-elevated CRP may be used to discriminate between the different AKI etiologies in the right context, provided that the patient is not on corticosteroids exceeding physiological doses [ 7 ].…”
mentioning
confidence: 99%